Ideology, scientific literacy, and climate change: the case of Spain - J. L. Arroyo-Barrigüete; C. Bellón Núñez-Mera; J. Labrador; V. L. De Nicolas (Journal of Environmental Studies and Sciences, 2023)

“Right diet for the right person”: a focus group study of nutritionist-dietitians’ perspectives on nutritional genomics and gene-based nutrition advice - Jacus S. Nacis; Marilou R. Galang; Jason Paolo H. Labrador; Milflor S. Gonzales; Aurora Maria Francesca D. Dablo; Diana Glades A. Domalanta-Ronquillo; Victor Franco J. Alfonso; Idelia G. Glorioso; Marietta P. Rodriguez (Journal of Community Genetics, 2022)
Advances in nutritional genomics are intended to revolutionize nutrition practice. A basic understanding of nutritional genomics among nutritionist-dietitians is critical for such advancements to occur. As a precedent to the development and integration of gene-based nutrition advice, this study aimed to assess hospital-based nutritionist-dietitians’ perceptions of nutritional genomics. A total of ten focus group discussions (FGDs) with sixty-one registered nutritionist-dietitians (RNDs) from hospitals in the National Capital Region (NCR), Philippines, were conducted from October to November 2019. Data were collected using a pretested semistructured discussion guide, and thematic analysis was subsequently performed. Diverging perceptions about nutritional genomics were noted among the FGD participants. Five themes emerged relating to the enablers and barriers of gene-based nutrition advice: training and capacity building, the extent of information to be disclosed, cost, ethical considerations, and government support. Themes related to the desired features of the gene-based nutrition advice included being consent-driven, cost-effective, technology-oriented, and guided by standards. The results of this study suggest that training and continued learning will equip RNDs to provide nutrition advice based on genetic information. However, other factors, such as cost and ethical considerations, are critical dimensions that need to be acknowledged and addressed before integrating gene-based advice into nutrition practice.

β-(1,4)-Galactan remodelling in Arabidopsis cell walls affects the xyloglucan structure during elongation - María Moneo-Sánchez; Alejandro Alonso-Chico; J. Paul Knox; Berta Dopico; Emilia Labrador; Ignacio Martín (Planta, 2019)

An Overview of the Regional Experiments for Land-atmosphere Exchanges 2012 (REFLEX 2012) Campaign - Wim J. Timmermans; Christiaan van der Tol; Joris Timmermans; Murat Ucer; Xuelong Chen; Luis Alonso; Jose Moreno; Arnaud Carrara; Ramon Lopez; Fernando de la Cruz Tercero; Horacio L. Corcoles; Eduardo de Miguel; et al. (Acta Geophysica, 2015)

Classification of floodplain vegetation by data fusion of spectral (CASI) and LiDAR data - G. W. Geerling; M. Labrador‐Garcia; J. G. P. W. Clevers; A. M. J. Ragas; A. J. M. Smits (International Journal of Remote Sensing, 2007)

The strength of integrin binding between neutrophils and endothelial cells - V. Labrador; P. Riha; S. Muller; D. Dumas; X. Wang; J. F. Stoltz (European Biophysics Journal, 2003)

Internal initiation of translation efficiency in different hepatitis C genotypes isolated from interferon treated patients - J. C. Sáiz; S. López de Quinto; N. Ibarrola; F.-X. López-Labrador; J.-M. Sánchez-Tapias; J. Rodés; E. Martínez-Salas (Archives of Virology, 1999)

Brassinolides promote the expression of a new Cicer arietinum β-tubulin gene involved in the epicotyl elongation - Francisco J. Muñoz; Emilia Labrador; Berta Dopico (Plant Molecular Biology, 1998)

Two growth-related organ-specific cDNAs from Cicer arietinum epicotyls - Francisco J. Muñoz; Berta Dopico; Emilia Labrador* (Plant Molecular Biology, 1997)